PENINGKATAN WAWASAN PENDIDIKAN ANAK USIA DINI MELALUI STRATEGI BELAJAR OUTDOOR - Hardianika Rahmaningtyas; Dini Rakhmawati; Arri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Early childhood education has a crucial role in forming the basis of child development. This article discusses innovative strategies for increasing insight into early childhood education through the application of outdoor learning. This research aims to explore the potential of outdoor learning as a means of stimulating children's creativity, physical abilities and social-emotional development. Through this approach, it is hoped that children can learn in a more holistic and enjoyable way.